Development and challenges of smart actuators based on water-responsive materials. Issue 31 (29th July 2022) - Zhang, Yiwei; Zhang, Chuang; Wang, Ruiqian; Tan, Wenjun; Gu, Yanyu; Yu, Xiaobin; Zhu, Lizhong; Liu, Lianqing
Abstract : This review has highlighted the WR properties of different materials and their related actuators, which may exhibit remarkable performance in various fields, such as artificial muscles, smart sensors, robots, and new energy generators. Abstract : Water-responsive (WR) materials, due to their controllable mechanical response to humidity without energy actuation, have attracted lots of attention to the development of smart actuators. WR material-based smart actuators can transform natural humidity to a required mechanical motion and have been widely used in various fields, such as soft robots, micro-generators, smart building materials, and textiles. In this paper, the development of smart actuators based on different WR materials has been reviewed systematically. First, the properties of different biological WR materials and the corresponding actuators are summarized, including plant materials, animal materials, and microorganism materials. Additionally, various synthetic WR materials and their related applications in smart actuators have also been introduced in detail, including hydrophilic polymers, graphene oxide, carbon nanotubes, and other synthetic materials. Finally, the challenges of the WR actuator are analyzed from the three perspectives of actuator design, control methods, and compatibility, and the potential solutions are also discussed. This paper may be useful for the development of not only soft actuators that are based on WR materials, but also smart materials applied to renewable energy.